Perceptual Not Attitudinal Factors Predict the Accuracy of Estimating Other Women’s Bodies in Both Women With Anorexia Nervosa and Controls - Gledhill, Lucinda J.; George, Hannah R.; Tovée, Martin J. (Frontiers in Psychology, 2019)
Disturbance in how one’s body shape and size is experienced, usually including over-estimation of one’s own body size,isa core feature of the diagnostic criteria of anorexia nervosa (AN). Is this over-estimation specific to women with AN’s judgements of their own body? Or is it just a general feature of their judgements about all bodies. If the latter, it would be consistent with a general error in the perception of body size potentially linked to the use of a different set of visual cues for judging body size. If the former, then this suggests that the over-estimation of own body size has a strong attitudinal component and may be part of the psycho-pathology of their condition. To test this hypothesis, 20 women with AN and 80 control observers estimated the body size of 46 women. The results show a strong effect of perceptual factors (contraction bias) in estimating body size for both controls and women with AN. This result is consistent with size over-estimation of own body in AN having an attitudinal basis and being a core feature of the psycho-pathology of the condition.